Multimanned partial disassembly line balancing optimization considering end-of-life states of products and skill differences of workers. (February 2023) - Yin, Tao; Zhang, Zeqiang; Wu, Tengfei; Zeng, Yanqing; Zhang, Yu; Liu, Junqi
Abstract: End-of-life states of waste products and skill differences of workers are the important factors affecting the production efficiency of disassembly lines and the workload balance of workers. The comprehensive effect of these two factors is considered for the first time in this study. The existing multimanned disassembly line balancing studies have focused on complete disassembly, i.e., all parts must be removed, while this study proposes a multimanned partial disassembly line balancing problem (MP-DLBP) to allow the worthless parts not to be removed and thus avoid invalid work and labour waste. Then, a mixed-integer programming (MIP) model is established to minimize cycle time and idle balancing index and maximize disassembly profit under the fixed number of open workstations. To obtain excellent solutions, an improved NSGA-II based on an incentive strategy (INSGA-II) is proposed to optimize the large-scale MP-DLBPs. Correctness of the model and INSGA-II are verified by comparing the experimental results of a demo product solved by CPLEX and INSGA-II. Superior performance of the INSGA-II for other DLBPs is verified by comparing the results of two actual disassembly instances and 19 generated instances of different scales solved by various algorithms in the existing literature. Finally, the INSGA-II is applied to the MP-DLBP of scrap printers. The superiority of INSGA-II for the printer case and the enhancement effect of incentive strategy are verified by comparing the optimization results with other two algorithms and their improved algorithms. Further, the relative conflict relationship between disassembly profit and idle balancing index is revealed, and the Pareto optimal solution set is provided for decision-makers. Highlights: Multimanned partial disassembly line balancing problem is proposed. Comprehensive effect of EOL states of waste product and skill differences of worker. Mixed-integer programming model is established. Improved NSGA-II based on the incentive strategy is proposed. Correctness of MIP model and superiority of INSGA-II are verified.